The Impact of Nutrition on Performance and Health of Badminton Athletes: A Literature Review - Rusdiar Rusdiar; Arsil Arsil; Umar Umar; Ahmad Chaeroni (Jurnal Penelitian Pendidikan IPA, 2024)
Badminton is a physically demanding sport that requires a combination of speed, agility, endurance, and strength. This literature review investigates the impact of nutrition on the performance, recovery, and long-term health of badminton athletes. A systematic search was conducted in major academic databases, including Scopus, ScienceDirect, and Google Scholar, using the keywords “badminton,” “nutrition,” and “athlete.” Studies published within the last ten years were selected to ensure the information was current and relevant to the sport. Key topics examined include macronutrients (carbohydrates, proteins, fats), micronutrients (calcium, iron, vitamin D, magnesium), hydration, and nutritional timing. Carbohydrates are identified as the primary fuel source, essential for sustaining high-intensity efforts and endurance during matches. Protein plays a critical role in muscle recovery and repair, while fats provide a reserve energy source for prolonged training or competition. Micronutrients like calcium, iron, and magnesium are crucial for bone health, oxygen transport, and muscle function. Proper hydration is equally important to maintain performance, reduce fatigue, and prevent muscle cramps. Nutritional timing—consuming specific nutrients before, during, and after exercise—can optimize energy stores, improve endurance, and accelerate recovery. Despite the clear benefits of nutrition in enhancing performance, many athletes still exhibit gaps in nutritional knowledge, which can lead to suboptimal dietary practices. This review emphasizes the importance of balanced, well-timed nutrition strategies and highlights the need for improved nutrition education to help badminton athletes maximize their performance, prevent injuries, and support long-term health.